Study of the Antibacterial Properties of a Composition Based on Chitosan Obtained from Dead Bees Apis Mellifera. (2022) - A., K.; Nurutdinova, Nurutdinova; M., F.; Ikhtiyarova, Ikhtiyarova; A, G.
No abstract available